Voluntary premarital screening to prevent sickle cell disease in Jamaica: does it work? - Serjeant, G. R. (J Community Genet, 2017)
To determine whether identifying haemoglobin genotype, and providing education and counselling to senior school students will influence their choice of partner and reduce the frequency of births with sickle cell disease. The Manchester Project provided free voluntary blood tests to determine haemoglobin genotype to the fifth and sixth forms (grades 11–13), median age of 16.7 years, of all 15 secondary schools in the parish of Manchester in south central Jamaica. A total of 16,636 students complied, and counselling was offered to carriers of abnormal genes over 6 years (2008–2013). The genotypes of their offspring were determined by newborn screening of 66,892 deliveries in 12 regional hospitals over 8 years (2008–2015). The study focused on the genotypes of live deliveries to female students with the four most common haemoglobin genotypes: 7905 with an AA genotype, 898 with the sickle cell trait, 326 with the HbC trait and 78 with the beta thalassaemia trait. A total of 2442 live deliveries were identified by the end of 2015 in mothers screened at school. Eleven babies had clinically significant genotypes, and the prevalence of SS and SC disease did not differ from that predicted by random mating. First pregnancy was not delayed in AS or AC mothers. There was no evidence that knowledge of maternal haemoglobin genotype influenced choice of partner. On an interview, mothers of affected babies correctly recalled their genotype, but either did not discuss this with their partners or the latter refused to be tested. Subjects delaying child bearing for tertiary education would be largely excluded from the present study of first pregnancies and may make greater use of this information. Future options are a greater role for prenatal diagnosis.